Sexuality at the Time of Coronavirus in Italy: A (Technological) Retreat in Itself? - Costantino Cipolla (Culture e Studi del Sociale)
Our contribution aims at unravelling the knot between sexuality and the web in Italy during the coronavirus pandemic. Sex-related online practices intensified, due to health concerns and lockdown measures, and access to pornographic websites skyrocketed. What is the cultural, relational, and psychological impact of this? We identify two main outcomes: widespread solipsism and dissolution by excess. It is, to the best of our knowledge, an unexplored territory. Sociologists did not address previous pandemics, nor have they provided extensive and methodologically satisfying work on sexuality in Italy. Given the delicate nature of the topic, and the unreliability of traditional sociological research methods, we chose to fully carry out our research online. We will examine online prostitution, webcam girls, user-produced pornography and dating sites, in addition to touching upon other topics such as sexting. We will, to the best of our abilities, try to mark a path in the wilderness of human sexuality in the digital era and in these unprecedented circumstances. We believe that the link between online and offline sexuality will be consolidated and define this relationship as differentiated integration: a reciprocal adaptation covering the most diverse places and ways. To study this web-integrated society, we propose the eclectic approach.